Comparative efficacy of agomelatine versus sertraline in major depressive disorder in Himalayan region of India - Mehta, Anil Kumar; Gupta, D. D.; Kumar, Ramesh; Sood, Atal (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Depression, a major common affective disorder which carries excess mortality through suicide. Among various drug classes available SSRI’s are usually a choice, but many patients show inadequate response, residual symptoms or discontinue medication due to intolerable side effects. Disturbances of circadian rhythm function are an etiopathogenic hallmark of depression. The degree of circadian misalignment correlates with the severity of depression and circadian abnormalities may partially be a consequence of alterations in behavior and sleep patterns that accompany depression. Agomelatine an agonist acts on MT1 and MT2 receptors and antagonist of 5HT2c receptors contributes to its resynchronization of circadian rhythms, enhancement of dopaminergic and adrenergic input to the frontal cortex, induction of hippocampal neurogenesis, and ultimately, to its antidepressant effect. Methods: The study was randomized, prospective, comparative and interventional regarding the efficacy of therapy. Hundred consenting patients of MDD attending psychiatry OPD were screened for possible enrollment into group A(Agomelatine) and group B(Sertraline). Patients were assessed by semi-structured case recording form, DSM-IV- TR Criteria for major depressive episode, Hamilton Rating Scale for Depression (HAM-D) and Clinical Global Impressions for severity (CGI-S) at baseline and CGI for improvement (CGI-I), every two weeks interval and final assessment at 8 weeks. Results: Socio-demographic parameters like age and sex distribution, marital status, locality, family type, educational status, occupation and socio-economic class were comparable between two groups. Similarly baseline HAM-D and CGI-S values between the two groups were statistically non-significant. HAM-D, CGI-S and CGI-I values at eight weeks among the two groups were also statistically non-significant but in all three sertraline had decreased the values to a greater extent and showed a trend towards improvement. Conclusions: Both groups had shown significant decrease in scores of all scales i.e. HAM-D, CGI-S, and CGI-I at the end of 8th week as compared to baseline scores, indicating that the uses of agomelatine and sertraline have resulted in significant improvement in symptoms of patients of MDD and reinforcing there efficacy in treatment of MDD. No statistical difference was observed between two groups.